FACEBOOK USAGE: AN EXPLORATORY STUDY OF STUDENTS IN ACEH - Yusoff, Mohammad MD; Bhakti, Sufri Eka (Fakultas Ushuluddin Adab dan Dakwah IAIN Lhokseumawe, 2020)
Social media such as Facebook, Instagram, WhatsApp, and Twitter allows millions of students to create their profiles and also learn about bridging and bonding relationship. Using the uses and gratifications approach, this research explores a study about common typologies of Facebook use generally. This exploratory study examined students through surveys and in-depth interviews on Acehnese Students Community. This theory is expected to help communication researchers better understand the powerful influence Facebook has on students. Based on the results acquired through the quantitative questionnaire approach, it was discovered that there were three typologies, which were information, entertainment, and social interaction underlying Facebook usage. Therefore, many students shared that they used Facebook as a social interaction tool, an information source, and entertainment.